The Lexical Errors Committed by Undergraduate English Learning Students in the University of Mali and Mari State University (Russia) - Mariko, Mohamed Lamine (International Journal of Psychosocial Rehabilitation, 2020)
This study is limited to the incorrect lexical selections, which are hindering the quality of the students’ written communication. The limitation is designed to be such because the written communicative quality of English being learned as a second language (ESL) is evidence of how successful the learning, if not, the teaching is proceeding. The justification of the choice of this scope is because of the importance of lexical selections, when they are wrong, this phenomenon will be harmful not only to the message in its content. The taxonomy by James (1998), Hemchua and Schmitt (2006) was used to detect and categorize the irrelevant lexical errors among the participants. As such, the most frequent errors the students face in their French-English translation are formal errors (namely, borrowing: 22, 81%; coinage: 14, 58%) and semantic errors (under specification: 48%; semantic word selection:35%).